The RNA-binding protein RBPMS inhibits smooth muscle cell–driven vascular remodeling in atherosclerosis and vascular injury - Jianlin Du; Xin Yuan; Jiajia Wang; Lujun Zhang; Fangyan Tan; Tianyang Hu; Xingsheng Li; Fan Liu; Haitao Ran; Zhigang Wang; Yongyong Li; Yuxing Feng; et al. (Proceedings of the National Academy of Sciences, 2025)
Atherosclerosis and vessel wall trauma induce vascular smooth muscle cell (VSMC) phenotypic modulation, leading to plaque cap growth and postintervention restenosis. Our systems biology approach identified RNA binding protein, mRNA processing factor ( RBPMS ) as a conserved, VSMC-specific gene associated with VSMC modulation in atherosclerosis. RBPMS gene expression positively correlates with VSMC contractile markers in human and murine atherosclerotic arteries as well as in two vascular injury models during the postinjury intimal hyperplasia phase. RBPMS promotes contractile VSMC differentiation, reduces plaque cap development in high-fat diet-fed apolipoprotein E-null ( ApoE −/− ) murine atherosclerotic arteries, and inhibits intimal hyperplasia. Mechanistically, the RBPMS protein interacts with the myocardin ( MYOCD ) pre-mRNA and enhances MYOCD_v3 / MYOCD_v1 transcript balance through alternative exon 2a splicing. RBPMS promotes the VSMC contractile phenotype and reduces their fibroproliferative activity in a MYOCD_v3a-dependent manner. RBPMS enhances Myocd_v3 / Myocd_v1 transcript balance in both atherosclerotic and injured vessels. RBPMS may inhibit VSMC-driven plaque cap development and intervention-induced restenosis.